Overexposure to Benzodiazepines: the irony in psychiatric treatment - Sadia, Haleema (Journal of the Pakistan Medical Association, 2025)
Dear Madam, With the growing mental health awareness culture, youth today have a great level of exposure to diagnostic techniques and medications, leading to a drastic increase in the phenomenon of self-prescription of otherwise meant to be regulated pharmaceutical solutions. The average price of 30 tablet pack of 5 mg diazepam, the usual benzodiazepine popularly known as “tension relievers” is about Rupees 20 (approx. 7.2 cents), which is inexpensive even given the low per capita income in Pakistan.1 With benzodiazepines being this readily available for such affordable prices, one must question the inducive effect this has on the dependence on benzodiazepines and its misuse, simultaneously increasing the risk of self-poisoning. A study conducted in a psychiatry outpatient setting reported a 45% prevalence of benzodiazepine use in Pakistan. Amongst which, self-medication in our study population came alarmingly high at 58(16%).2 This benzodiazepine overexposure presents a worrying irony indeed. Initially provided to (or self-administered) to relieve anxiety and improve emotional stability, their overuse frequently results in a cascade of negative effects, including increased depression, increased anxiety, emotional instability, and cognitive deterioration. What begins as a therapeutic intervention can eventually aggravate the very issues it seeks to alleviate. Findings state only a minority (11%) of pharmacies required a script to dispense psychotropic medications, with most pharmacy staff (78.5%) unaware of these drugs’ abuse potential.3 Thus the misuse can also be partially credited to the lack of regulation regarding non-prescription based over-the-counter sales of benzodiazepines, while the rest is addressed to overworked and untrained health professionals opting for shorter treatment routes as opposed to time demanding long term therapeutic interventions. Advice and follow-up on sleep hygiene and investigating and addressing etiological factors may be more effective strategies for ameliorating sleep problems than prescription of sleep aids which have the potential for abuse and dependency, especially given the statistically supported unregulated and easy availability of hypnotics and benzodiazepines in Pakistan.4 If such measures are not put into action, as a growing population with alarmingly high mental health issues, we will fall into a cycle of addiction, treating one psychological problem by adopting another" for clarity and grammatical accuracy (gaining an addiction as the price for curing depression).